Crime, compulsory schooling laws and education - Bell, B; Costa, R; Machin, S (Elsevier, 2015)
Do compulsory schooling laws reduce crime? Previous evidence for the US from the 1960s and 1970s suggests they do, primarily working through their effect on educational attainment to generate a causal impact on crime. In this paper, we consider whether more recent experience replicates this. There are two key findings. First, there is a strong and consistent negative effect on crime from stricter compulsory schooling laws. Second, there is a weaker and sometimes non-existent link between such laws and educational attainment. As a result, credible causal estimates of the education–crime relationship cannot in general be identified for the more recent period, though they can for some groups with lower education levels (in particular, for blacks).